PENGERASAN (HARDENING) RODA GIGI SPROCKET SEPEDA MOTOR DENGAN VARIASI WAKTU PENAHANAN DAN MEDIA PENDINGIN - Kris Witono; Subagiyo Subagiyo (INFO-TEKNIK, 2017)
Motorcycle problems with large (cylinder / cc) engines are generally located on the sprocket gears that are rapidly wearing wear. The objective of this study was to increase the hardness of sprocket gears, while improving their wear resistance through hardening heat treatment process with variation of holding time and cooling medium. The research method included heating the specimen up to its critical temperature (850 ° C), retained with variations of holding time of 30, 60, and 90 minutes, then cooled rapidly (quenching) on water cooling, brine, and oil variations. The results showed an increase in the hardness of sprocket gears, with maximum hardness increases occurring at 30 minutes and 30 minutes of brine cooling.